A confirmatory factor analysis of the beck anxiety inventory in Latinx primary care patients. Issue 4 (1st October 2020) - Benuto, Lorraine T.; Zimmermann, Martha; Gonzalez, Frances R.; Corral Rodríguez, Andrea
Abstract: Research on the Beck Anxiety Inventory (BAI) with ethnic minorities in the U.S. is limited. Because Latinxs constitute 18% of the U.S. population and are the second largest ethnic group in the country, the current study replicated the aforementioned study and examined the BAI factor structure with a Spanish-speaking Latinx sample in the United States. We investigated the original two-factor structure of the BAI with 149 Spanish-speaking Latinx primary care patients. Results from a confirmatory factor analysis indicated that the previous factor structures of the BAI did not represent an adequate fit for our sample. An exploratory factor analysis indicated that possibly an alternate two-factor model of anxiety was the best fit for the data. Cultural considerations are discussed including the possibility of utilizing cultural idioms of distress as a way to assess anxiety among Latinxs.